Analisis Strategi Pemasaran Kopi Arabika Bergendaal Koffie di Kabupaten Bener Meriah - Mirza Fahmi; Akhmad Baihaqi; Irwan Irwan (Jurnal Agrisep, 2013)
ABSTRACT. Economic globalization and free trade are signified by hard competition that pushing the industries to increase their productivity and product quality result, that is why we need to analyze business management especially marketing strategic. The research was done at Bergendaal Koffie, in Simpang Teritit, Bener Meriah District. The object of research is marketing strategic data that competitive at Bergandaal Koffie. The purpose of this research was to know marketing strategy at Bergendaal Koffie by using SWOT (Strenght, Weakness, Opportunity, and Threat) analysis tool are consist of SAP (Strategy Advantage Profile) analisys and ETOP (Environmental Threat Opportunity Profile). SAP analysis to Bergendaal Koffie industry is placed in secure competition position (Favourable) and ETOP analysis show that Bergendaal Koffie industry including Speculative Business. Combination of those two matrixs in SWOT shows in the infestation position. It means that optional of good strategy that could be implemented by Bergendaal Koffie industry is doing invest to harvest, the meaning is to invest for the short term and then reaping the reward of this investment in the future.